2018
DOI: 10.3329/sja.v15i2.35146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought stress on water relation traits of four soybean genotypes

Abstract: An experiment was conducted in a venyl house at the environmental stress site of Bangabandhu Sheikh Mujibur Rahman Agricultural University during September to December 2012 to know the internal water status under drought stress in soybean genotypes, viz. Shohag, BARI Soybean-6, BD2331 (relatively stress tolerant) and BGM2026 (susceptible). Drought (water) stress reduced the leaf water potential in all the genotypes though was more negative in tolerant genotypes than in susceptible ones. The lowest leaf water p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 8 publications
4
24
0
Order By: Relevance
“…It was observed that drought conditions have negative impact on water balance, and hence decrease the water potential of leaves. Therefore, RWC indicates the degree of drought stress, as previous studies have reported that higher decreases in water potential were observed in drought-susceptible varieties than in drought-tolerant varieties (Parvin et al, 2015; Chowdhury et al, 2017) .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It was observed that drought conditions have negative impact on water balance, and hence decrease the water potential of leaves. Therefore, RWC indicates the degree of drought stress, as previous studies have reported that higher decreases in water potential were observed in drought-susceptible varieties than in drought-tolerant varieties (Parvin et al, 2015; Chowdhury et al, 2017) .…”
Section: Resultsmentioning
confidence: 89%
“…It was observed that drought conditions have negative impact on water balance, and hence decrease the water potential of leaves. Therefore, RWC indicates the degree of drought stress, as previous studies have reported that higher decreases in water potential were observed in drought-susceptible varieties than in drought-tolerant varieties (Parvin et al, 2015;Chowdhury et al, 2017). In this study, the highest percentage decrease in RWC was observed in varieties TARM-1 (19.52%) and PDM-139 (16.6%); the lowest percentage decrease in RWC was recorded in varieties MCV-1 (1.82%) and V. sublobata (1.5%) during the vegetative and reproductive stages, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…A previous study supports the results presented here, where unprimed control seeds recorded the highest value; whereas, the seeds primed with SA had the lowest recorded value in maize [ 31 ]. An increase in electrolyte leakage, which reflects a loss in the ability of biological membranes to regulate the transport of ions, has been reported in soybeans under drought stress [ 82 ]. Seeds primed with phenylalanine or calcium nitrate had the lowest electrical conductivity readings, suggesting lower degrees of cell injury [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the size of the cells is a very common anatomical variation found in leaves under water stress condition [28]. Lowest reduction of water in genotypes of soybean namely Shohag and BARI Soybean-6 which indicate their tolerance capability under water stress phenomenon [29]. Faster the establishment potential of the mungbean genotypes, the greater the germination co-efficient.…”
Section: Discussionmentioning
confidence: 99%